2021
DOI: 10.21203/rs.3.rs-753249/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Connectivity Density Alterations in Children with Strabismus and Amblyopia based on Resting-state Functional Magnetic Resonance Imaging (fMRI)

Abstract: Purpose: To investigate functional connectivity density (FCD) values of brain areas in children with strabismus and amblyopia (SA) by resting-state functional magnetic resonance imaging (rs-fMRI).Methods: This study recruited 26 children (14 male, 12 female) with SA and 26 healthy children (14 male, 12 female) as healthy controls. Both groups matched in age, gender, educational level and socioeconomic background. All participants underwent fMRI scanning while resting. Visual function of participants was also e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the correlation analysis between the ROIs and behavioral performance (accuracy) in a key-press decision task, it was observed that in the NG group, activation in the left rectus gyrus, bilateral thalamus, and left temporal pole showed a significant negative correlation with accuracy during the keypress decision phase. The rectus gyrus is associated with episodic memory (Feng et al, 2020), the thalamus is involved in visual information processing (Shi et al, 2022), and the temporal pole plays an important role in perceptual processing (Bangert and Altenmuller, 2003). This finding suggests that the activation in these brain regions in the novice group may be associated with lower decision-making ability or uncertainty, leading to decreased accuracy in decision-making behavior.…”
Section: Behavioral Expression and Brain Activation During Button Dec...mentioning
confidence: 99%
“…In the correlation analysis between the ROIs and behavioral performance (accuracy) in a key-press decision task, it was observed that in the NG group, activation in the left rectus gyrus, bilateral thalamus, and left temporal pole showed a significant negative correlation with accuracy during the keypress decision phase. The rectus gyrus is associated with episodic memory (Feng et al, 2020), the thalamus is involved in visual information processing (Shi et al, 2022), and the temporal pole plays an important role in perceptual processing (Bangert and Altenmuller, 2003). This finding suggests that the activation in these brain regions in the novice group may be associated with lower decision-making ability or uncertainty, leading to decreased accuracy in decision-making behavior.…”
Section: Behavioral Expression and Brain Activation During Button Dec...mentioning
confidence: 99%